Dampak Perubahan Sosial Terhadap Manajemen Pendidikan Islam di Indonesia - Yusraini, Yusraini; As'ad, As'ad; Jamrizal, Jamrizal (El-Ghiroh : Jurnal Studi Keislaman, 2023)
This study aims to determine the impact of social change on the management of Islamic education in Indonesia. The method used is using qualitative exploration. The result obtained is that social-social change is a side effect of changes in social design and social examples with social demand. Islamic education plays a major role in change for the better, because Islamic education has formed individuals who have self-confidence, ethical quality, foster personality, establish social relationships, are sincerely and deeply healthy, so they are able to protect themselves and will try to bring about change. on society. We also see an increase in knowledge and innovation in social change lies in management, especially the management of Islamic education because of changes in the eyes of society, so there are many hopes for schools/madrasas that focus on the direction of science and innovation. Where people need educational organizations that keep up with progress in education management so that they can provide the best graduates.